2020
DOI: 10.3389/fpls.2020.579376
|View full text |Cite
|
Sign up to set email alerts
|

The Whys and Wherefores of Transitivity in Plants

Abstract: Transitivity in plants is a mechanism that produces secondary small interfering RNAs (siRNAs) from a transcript targeted by primary small RNAs (sRNAs). It expands the silencing signal to additional sequences of the transcript. The process requires RNA-dependent RNA polymerases (RDRs), which convert single-stranded RNA targets into a double-stranded (ds) RNA, the precursor of siRNAs and is critical for effective and amplified responses to virus infection. It is also important for the production of endogenous se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 109 publications
(201 reference statements)
1
23
0
Order By: Relevance
“…Aberrant transgenic transcripts also induce silencing amplification. In contrast, endogenous mRNAs and the cleavage products of miRNA-programmed RISC (miRISC) do not trigger amplification in wild-type plants (de Felippes and Waterhouse 2020 ; Tan et al 2020 ). However, if any of the RNA degradation systems, the decapping-XRN4, the SKI-exosome or the NMD system is impaired (and especially if both the XRN4 and the SKI-exosome exonucleases are inactivated) detrimental secondary siRNAs (called rqc- or ct-siRNAs) are generated from silencing prone mRNAs and miRNA targets (Mourrain et al 2000 ; Souret et al 2004 ; Moreno et al 2013 ; Branscheid et al 2015 ; De Alba et al 2015 ; Lam et al 2015 ; Wu et al 2020 ; Zhang et al 2015 ; Zhao and Kunst 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant transgenic transcripts also induce silencing amplification. In contrast, endogenous mRNAs and the cleavage products of miRNA-programmed RISC (miRISC) do not trigger amplification in wild-type plants (de Felippes and Waterhouse 2020 ; Tan et al 2020 ). However, if any of the RNA degradation systems, the decapping-XRN4, the SKI-exosome or the NMD system is impaired (and especially if both the XRN4 and the SKI-exosome exonucleases are inactivated) detrimental secondary siRNAs (called rqc- or ct-siRNAs) are generated from silencing prone mRNAs and miRNA targets (Mourrain et al 2000 ; Souret et al 2004 ; Moreno et al 2013 ; Branscheid et al 2015 ; De Alba et al 2015 ; Lam et al 2015 ; Wu et al 2020 ; Zhang et al 2015 ; Zhao and Kunst 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports suggested that RNA cleavage is required for transitivity (Carbonell et al 2012;Yoshikawa et al 2005). However, other studies challenge this assumption, arguing that cleavage is dispensable for the onset of transitivity (Arribas-Hernandez et al 2016;de Felippes et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Despite considerable progress, the exact mode of action of sRNAs on transitivity remains largely unaddressed (de Felippes and Waterhouse 2020). This is because transitivity studies in plants have been based so far on (1) transgenes expressing hairpin RNAs (hpRNAs) or inverted repeats (IRs), which are processed into a plethora of siRNAs, undermining any attempt to allocate specific roles to discrete siRNAs (Bleys et al 2006a; Bleys et al 2006b; Koscianska et al 2005; Vaistij et al 2002; Vermeersch et al 2010; Vermeersch et al 2013), (2) endogenous micro RNAs (miRNAs), which induce transitivity at very specific endogenous loci and thus exhibit a mode of action hardly reflecting a more generalized process (Axtell et al 2006; Montgomery et al 2008a; Montgomery et al 2008b), and (3) artificial miRNAs (amiRNAs), whose artificial long RNA precursor molecules are generally misprocessed into more than a single amiRNA (Chen et al 2010; Cuperus et al 2010; Manavella et al 2012; McHale et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This process has earlier been described and starts with the conversion of (aberrant) single stranded RNAs, resulting from primary RNA target cleavage, into small RNA profiling in suceptible and Ty-1 plants dsRNAs by the action of RDRs. Their subsequent processing by DCLs leads to a pool of secondary siRNAs and spreading of the siRNAs into the neighbouring sequences from the initial target sequences, called transitivity (de Felippes and Waterhouse, 2020). An alternative explanation is that in Ty-1 plants the expression pattern of viral genes might be changed, resulting in different amounts of templates to generate vsiRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Plants in which RDR6 has been knocked out generally become hypersusceptible to RNA viruses (Donaire et al, 2008;Schwach et al, 2005). RDR activity also leads to spreading of the silencing signal into sequences neighbouring the initially targeted sequence, a process called transitivity (de Felippes and Waterhouse, 2020;Parent et al, 2015). Like RDR6, RDR1 enhances the antiviral PTGS pathway, but it's function is less understood (Donaire et al, 2008;Garcia-Ruiz et al, 2010;Qi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%